The Bank of Canada's Monetary Policy Framework : Have Recent Changes Enhanced Central Bank Credibility? - Ito, Takatoshi; Gonzalez-Hermosillo, Brenda (Washington, D.C. : International Monetary Fund, 1997)
In recent years the Bank of Canada has made important changes in the way it conducts monetary policy. In particular, the bank has adopted explicit inflation targets and introduced significant changes to its operational framework designed to increase transparency and reduce market uncertainty. This paper examines the key issues associated with the recent changes in the Bank of Canada's monetary policy framework and analyzes various indicators of central bank credibility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet